Sensing Characterization of Helical Long Period Fiber Grating Fabricated by a Double-Side CO2 Laser in Single-Mode Fiber - Yujian Li; Ping Lu; Chi Zhang; Wenjun Ni; Deming Liu; Jiangshan Zhang (IEEE Photonics Journal)
A simple and efficient manufacture method of helical long period fiber grating (HLPFG) in a single-mode fiber (SMF) is designed and verified through experiment. Different from the previous fabricating methods, the SMF is heated by a double-side CO2 laser beam after being twisted. There are multiple transmission depletions caused by model coupling which could be observed when the period length is 500 μm. The sensing characteristics of the HLPFG have been investigated. Experimental results demonstrate axial strain sensitivities of 3.3 and 6.4 pm/μϵ at the selected dips in the range of 0–450 μϵ or temperature sensitivities of 35.3 and 49.5 pm/°C at the selected dips in the range of 20–70 °C, respectively. Moreover, through theoretical analysis, it is found that the fabricated HLPFG can measure axial strain and temperature concurrently by monitoring the resonance wavelength shift. Therefore, the fabricated HLPFG has brilliant applications value in dual measurement.